Stress related changes during TeamGym competition - De Pero, R.; Cibelli, G.; Cortis, C.; Sbriccoli, P.; Capranica, L.; Piacentini, M F. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: The aim of the present study was to investigate the stress-related changes of a TeamGym competition considering both physiological (i.e. salivary cortisol [sC] and alpha-amylase [sAA]) and psychological (i.e. state anxiety) responses in relation to exercise intensity and competition outcomes.